Suspended solids as drag reduction agents for liquid flow in a pipeline - Tania Suhail, Hadi (2011)
One of the major problems faced by the modern industrial applications is the power consumption and the limited power sources in the world. One of the most power consuming sectors in the industry is the liquid transportation through strategic pipelines for hundreds and thousands of miles. It is considered one of the most power dissipation industrial applications due to the turbulent mode these liquids are transported with. This is why; supporting pumping stations are assembled and located along the transportation pipeline to regain the pumping power lost during transportation. During the past century, many solutions for this problem were introduced. One of these solutions is the introduction of minute quantities of long chained polymeric additives that have the ability to interfere within the turbulent media formed inside the pipelines and reduce the power losses. The solubility and shear degradation of these polymers during transportation added more problems to the major problem to be solved. A more effective solution is needed. In the present investigation, three types of suspended solid materials, which are sand, aluminum and coal powders, are investigated as drag reducing agents to overcome the solubility problems that any new material finding to be recognized as drag reducing agent. Also, two types of commercially available zwitterionic surfactants ((3-(Decyldimethyl-ammonio) propanesulfonate inner salt) and (3-(N-N Dimethylpalmityl-ammonio) propanesulfonate) are investigated their efficiency in improving the suspended solid drag reducing abilities. An experimental closed loop liquid recirculation rig was built to carry out the experimental work. The rig consists of tanks, pumps, three pipes with three different diameters 0.0125, 0.0254 and 0.0381 m I.D. Each pipe was divided into four testing sections with 0.5 m length for each one. The flow rate of the transported water was measured using ultrasonic flow meter and the pressure drop measurement for each section was made using differential manometer. The powders were added within three different concentrations 100,300 and 500 ppm while the surfactants were added to the suspension solutions within three different concentrations 10, 20 and 30 ppm. The variables investigated in the present work were; the pipe diameter effect, the testing section length, the suspended solid type, the suspended solid concentrations, the suspended solid particle size two sizes were investigated 45 and 71 μm, the surfactant type, the surfactant concentrations and the solution flow rates. Using the suspended solids as drag reducing agents, the experimental results showed that, the powders can act as a powerful drag reducing agents and the Percentage of Drag Reduction (%Dr) increases by increasing the solution flow rate represented by the dimensionless form of Reynolds Number (Re). The %Dr was found to be higher for smaller pipe diameters and the testing section length didn’t show a noticeable effect on the powder performance as drag reducing agent. Maximum %Dr up to 38, 45 and 38% were observed for the sand, aluminum and coal powders respectively. The %Dr was found to increase by increasing the suspended solid concentrations inside the pipe. The values of the %Dr were higher for the larger particles size (71 μm). Generally, the aluminum powder showed the higher and more stable drag reduction performance compared with the other two powders investigated due to the powder density effect. The addition of the surfactants to the suspended solid solution improved its drag reduction performance up to 78% in certain cases. The drag reduction performance was found to increase by increasing the surfactant concentrations vi reaching certain maximum values up to (67, 67 and 69)% for DAPI and (64.5, 65.5 and 69.8)% for the NNAP added aluminum, coal and sand powders respectively. A numerical model (correlation) is derived and introduced as a mathematical representation for the experimental work. The final form was f=a(Re)b. Statistical analysis was applied for all the experimental data and compared with Virk’s asymptote. All the results were close enough to that asymptote and one of the correlation passed Virk’s asymptote with the form f=0.798Re-0.746.